2021
DOI: 10.5114/wiitm.2021.108216
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery in patients undergoing laparoscopic partial nephrectomy. Results from a real-world randomized controlled trial.

Abstract: Introduction: Enhanced recovery after surgery (ERAS) is a set of perioperative interventions to alleviate patients' stress response and complications, and to promote rehabilitation. Data on its implementation in renal cell carcinoma treated by laparoscopic partial nephrectomy are lacking. Aim: To evaluate the prospect of application of ERAS in laparoscopic partial nephrectomy based on real-world data. Material and methods: Sixty patients with T1a staging renal cell carcinoma (RCC) were randomly classified as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…Отмечен достоверно менее выраженный послеоперационный болевой синдром и риски развития послеоперационной тошноты и рвоты без увеличения риска реадмисии. Аналогичные выводы получены в исследованиях, посвященных сравнению стандартного лечебного подхода и протокола ускоренного выздоровления при резекции почки [9] и при донорской нефрэктомии [17]. При этом размер удаляемого органа не коррелирует напрямую с общим суммарным размером доступа и объемом операционной травмы при применении современного инструментария, шейвера или фрагментации удаляемой почки [18].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Отмечен достоверно менее выраженный послеоперационный болевой синдром и риски развития послеоперационной тошноты и рвоты без увеличения риска реадмисии. Аналогичные выводы получены в исследованиях, посвященных сравнению стандартного лечебного подхода и протокола ускоренного выздоровления при резекции почки [9] и при донорской нефрэктомии [17]. При этом размер удаляемого органа не коррелирует напрямую с общим суммарным размером доступа и объемом операционной травмы при применении современного инструментария, шейвера или фрагментации удаляемой почки [18].…”
Section: Discussionunclassified
“…Особенно следует отметить, что по данным иссле-дования продленная госпитализация не влияет на частоту осложнений и риск реадмиссии [8]. Применение ПУВ при выполнении резекции почки сопровождается лучшим послеоперационным статусом пациентов, менее выраженной болью, меньшим сроком госпитализации, риском развития осложнений со стороны желудочно-кишечного тракта [9,10].…”
unclassified
“…In clinical work, some doctors may have inertial thinking similar to asymptomatic UTUC and asymptomatic bladder cancer, and they are more inclined to perform kidney-retaining surgery. On the other hand, fast-track surgery and enhanced recovery after surgery has been widely adopted in the field of general surgery [ 15 ]. However, we found that the stage and grade of UTUC were not related to the presence of symptoms.…”
Section: Discussionmentioning
confidence: 99%